EVALUATION OF EMPLOYEE SELECTION PROCESS AT SAMBA BANK - Razan Mushaddak; Abdulquddus Mohammad (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Numerous associations in Saudi Arabia have set up extensive recruitment programs for employees. However, most associations do not put resources into time and effort to improve the choice strategy that will benefit the association. Individual supervisors and human resource management (HRM) authorities can add to their association’s prosperity by pursuing enhanced representative determination strategies. Therefore, this work was done to analyze employee selection process at SAMBA in Jeddah, Saudi Arabia. This work was conducted using quantitative and qualitative research method. The sample population of this work was 50 customers of SAMBA. Data collection was done based on survey method. In addition, two bank managers were interviewed. The finding of this work have shown that majority of the respondent have agreed that SAMBA employees are well qualified and trained. Furthermore, the results have shown that employees at SAMBA are helpful and hired in the right positions. The interview outcome has confirmed that SAMBA follows the international hiring processes while hiring employees. Therefore, it is deduced that SAMBA has practiced a viable recruitment and selection process for its employees